Assistive Device Needs for Children with Disabilities in Nepal: A Census Analysis - Bastola, Bidur (Journal of Health Promotion, 2025)
Children with Disabilities (CwD) in Nepal face widespread exclusion from formal education, primarily due to limited access to assistive devices. Although Article 31 of the Constitution of Nepal mandates an inclusive education policy ensuring the right to quality education for Persons with Disabilities (PwDs), many children with visual and hearing impairments in schools lack access to basic assistive devices. This study aims to estimate the need and associated costs for basic assistive devices for school-enrolled Children with hearing and visual impairments. Descriptive analysis of data from the Nepal Population and Housing Census (NPHC) 2021 using Statistical Package for Social Science (SPSS) and cost estimates based on the Priority Assistive Product List of Nepal 2018, the study provides essential insights into the resource requirements. The findings indicate that 114,671 school-enrolled children with visual and hearing impairments require basic assistive devices, with 35% in basic education and 19% in secondary education. The total estimated cost to meet this demand amounts to NPR 920,968,600. The study concludes by emphasizing the need for different tiers of government and decision-makers to critically review on their programmatic assumptions and policies to foster a more inclusive educational environment to address the assistive device needs for students with hearing and visual impairments. This research addresses a critical knowledge gap and offers actionable recommendations to improve educational access for CwD through policy implications.